Identification of a novel mitochondria-localized LKB1 variant required for the regulation of the oxidative stress response - Tan, Ivan (2023)
The tumor suppressor Liver Kinase B1 (LKB1) is a multifunctional serine/threonine protein kinase that regulates cell metabolism, polarity, and growth and is associated with Peutz-Jeghers Syndrome and cancer predisposition. The LKB1 gene comprises 10 exons and 9 introns. Three spliced LKB1 variants have been documented, and they reside mainly in the cytoplasm, although two possess a nuclear-localization sequence (NLS) and are able to shuttle into the nucleus. Here, we report the identification of a fourth and novel LKB1 isoform that is, interestingly, targeted to the mitochondria. We show that this mitochondria-localized LKB1 (mLKB1) is generated from alternative splicing in the 5' region of the transcript and translated from an alternative initiation codon encoded by a previously unknown exon 1b (131 bp) hidden within the long intron 1 of LKB1 gene. We found by replacing the N-terminal NLS of the canonical LKB1 isoform, the N-terminus of the alternatively spliced mLKB1 variant encodes a mitochondrial transit peptide that allows it to localize to the mitochondria. We further demonstrate that mLKB1 colocalizes histologically with mitochondria-resident ATP Synthase and NAD-dependent deacetylase sirtuin-3, mitochondrial (SIRT3) and that its expression is rapidly and transiently upregulated by oxidative stress. We conclude that this novel LKB1 isoform, mLKB1, plays a critical role in regulating mitochondrial metabolic activity and oxidative stress response.